Oktyabr'skiy uragan - Deni, Viktor (Плакат СССР (Plakat), 1967)
Building labelled capitalism with a capitalist shaped tower being knocked over and pillars representing the military, the orthodox church, SR's and Mensheviks collapsing, being blown over by red wind 1967 reproduction of 1920 poster art. Original title: Октябрьский ураган PO-1030